PENTINGNYA TEORI BELAJAR BAHASA DALAM MENGEMBANGKAN KEMAMPUAN BERBAHASA ANAK - Nursalim; Romadon, Ahmad; Firdaus Jimmi Pasaribu (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Language skills are a crucial aspect of elementary school children's development. Effective language learning can help children improve their communication skills, critical thinking skills, and literacy, which are the foundation for academic success. This article aims to review various literature related to the importance of language learning theories in developing children's language skills. Through a literature review approach, this research examines various methods, strategies, and challenges that arise in language learning, while also examining their impact on children's cognitive and social development. The results of this study indicate that language learning can help develop children's language skills, which can be developed daily through daily activities and can also improve children's cognitive and social abilities.